“Valoración polínica obtenida por Apis mellifera L. en colmenares del huallaga central-San Martín” - Ormeño Luna, Javier (2015)
The objective of the present research work was to determine the valuation of loads of pollen corbicular obtained by Apis mellifera L, based on pollen analysis; in order to evaluate the relationship between the botanical origin of pollen grains and pollen type present in the species of apicultura! flora from the environment of the apiaries of the season June-October 2015. The study was carried out in the period of June to December 2015, in Juanjui city, Mariscal Cáceres province, San Martín region. The fieldwork was developed in the apiaries environment where the referential flora was evaluated in full phase floral phenology, in the case of large flowers we directly took samples of grain of the anthers and the whole flower were processed in the case of the small ones (Traverse, 1998). In the laboratory, we used the technique of Erdtman acetolysis (1960) for the respective observations, measurements and identification-level family of pallen grains; the measurement was carried out with the aid of optical microscopy to 1000 x, su ch as notes Herngreen (1983); and the meas u res in polar and Equatorial view with 30 repetitions per species as mentioned by Huaman (1991 and 1993) and Mari (2000). On the samples of pallen corbicular were separated from agreement characteristics of color in arder to verify that each color group corresponds to the same taxon, microscope observations were following the method proposed by Hidalgo et to the. (1990). After the processing of samples of referential flora, pallen corbicular and honey, we identified 35 taxa, 15 of them were registered with its pallen type. The most dominant taxa that obtained more than 200 grains of pallen in the observed samples were: Arecaceae, Cannabaceae and Poaceae, of this last the predominant species was the pallen of corn (Zea mays L.). On the origins of honey; The Planicie sector was characterized a multi-flower honey consisting of Asteraceae (38.75%), Poaceae (24.67%), Tricolporado (19.00%) and registered 11 pallen types. In Villa Prado sector; a monofloral honey of Asteraceae were characterized (48.75%) and 13 pallen types were recorded.